Stakeholder Perspectives on a Culture of Health Key Findings - Acosta, Joie D. (RAND Corporation, 2016)
Since 2013, the Robert Wood Johnson Foundation has embarked on a pioneering effort to advance a Culture of Health in which "everyone in our diverse society leads healthier lives now and for generations to come." To put the Culture of Health vision into action, RAND Health supported development of an action framework and measurement strategy. This report summarizes the stakeholder engagement efforts RAND used to inform this work.